2022
DOI: 10.1002/adma.202109107
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization of Fluorescent Protein Exciton–Polaritons at Room Temperature

Abstract: Fluorescent proteins (FPs) have recently emerged as a serious contender for realizing ultralow threshold room temperature exciton–polariton condensation and lasing. This contribution investigates the thermalization of FP microcavity exciton–polaritons upon optical pumping under ambient conditions. Polariton cooling is realized using a new FP molecule, called mScarlet, coupled strongly to the optical modes in a Fabry–Pérot cavity. Interestingly, at the threshold excitation energy (fluence) of ≈9 nJ per pulse (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In one case, Satapathy et al reported thermalization of exciton-polaritons in a hybrid metaldielectric microcavity containing the fluorescent protein mScarlet. 181 Two samples were fabricated: one cavity with a Q-factor of 160 and another with a Q-factor of 330. When the low-Q sample was excited, the corresponding polariton distributions at different excitation fluences are well described by a Maxwell-Boltzmann distribution from 17.3 mJ/cm 2 up to the onset of photobleaching at 43.4 mJ/cm 2 [Fig.…”
Section: B Identifying Condensationmentioning
confidence: 99%
“…In one case, Satapathy et al reported thermalization of exciton-polaritons in a hybrid metaldielectric microcavity containing the fluorescent protein mScarlet. 181 Two samples were fabricated: one cavity with a Q-factor of 160 and another with a Q-factor of 330. When the low-Q sample was excited, the corresponding polariton distributions at different excitation fluences are well described by a Maxwell-Boltzmann distribution from 17.3 mJ/cm 2 up to the onset of photobleaching at 43.4 mJ/cm 2 [Fig.…”
Section: B Identifying Condensationmentioning
confidence: 99%
“…A promising means to enhance energy transport is to strongly couple excitons with photons forming quantum mechanical quasi-particles, called exciton-polaritons. , Conventional polaritonic structures employ planar microcavities where the optically active layer is embedded between metallic mirrors or distributed Bragg reflectors (DBRs). However, their relatively short lifetimes and low group velocities prohibit propagation over long distances . In contrast, a truncated all-dielectric photonic structure can support long-range propagation of nondissipative Bloch surface waves (BSWs) over hundreds of micrometers .…”
mentioning
confidence: 99%
“…The light–matter hybridization characteristics of polaritons can serve as an effective platform for both fundamental investigations and photonic device applications. That is, devices that take advantage of the strong nonlinearities inherent in the exciton component, along with the propagation of the photon component, can usher in a new generation of highly capable and compact photonic devices. Fabry–Perot cavity polariton systems have shown coherent interference with confined polariton states over moderate propagation distances (∼25 μm). However, a polariton condensate is required in those systems, which increases their complexity.…”
Section: Introductionmentioning
confidence: 99%